Budaya Pembacaan Surat Yasin pada Malam Jumat di Masjid Al-Mizan Kendari - Yusril; Imelda Wahyuni (CV Putra Publisher, 2023)
The research approach to studying Islam in this scientific work discusses something that has become a culture (routine practice), namely the reading of the Koran, Surah Yasin, which was born from communal practice as a form of social response from society or certain communities to the Koran. in this case the al-Mizan mosque in Kendari. Some of the congregation carry out routine yasinan activities on Thursday during the congregational maghrib prayer. The object of Islamic studies studied includes Islam as a source, in this case the text used is sourced from the holy book Al-Qur'an and Islam as an understanding, in this case the level of understanding of society, especially mosque congregations, towards Islam generally understands Islam as a religion that is rahmatan lil' natural. The approaches used are sociological, theological and historical approaches. The methods are diactonic, synchronic and problem solving methods, as well as empirical methods. Meanwhile, in the tafsir study method, researchers use the ijmali tafsir method of the propositions of the Qur'an and the Hadith of the Prophet. The technique uses analysis and interpretation techniques. The results of this research show that the mosque administrators created a yasinan program and the mosque congregation participated in it in order to make the mosque prosperous, strengthen friendships, create closeness and hope for rewards and blessings from Allah SWT.